Dinamika Populasi Pseudomonas solanacearum pada Rizosfer Tanaman Bukan Inang - Triwidodo Arwiyanto; Elizabeth Handini; Toekidjo Martoredjo (Jurnal Perlindungan Tanaman Indonesia, 1997)
Bacterial wilt caused by Pseudomonas solanacearum is a main limiting factor in the production of tobacco. The objective of this study is to investigate the survival of P. solanacearum in the rhizosphere of presumed nonhost plants. The results indicated that in the sugarcane rhizosphere, the pathogen population decreased along with the time course. The bacteria could not infect the root of sugarcane. On the other hand, the pathogen could infect the root of Mimosa invisa, although the population also decreased along with the time course.